Decision-making of college students in a sub-urban small Catholic college - Pasig Catholic College - Ursua, Rosalinda V. 1935- (s.n.], 1968)
The study inquired about the factors and processes involved in students' decision-making. The trends and patterns of decision-making of students with reference to their chosen course, college, and prospective occupation are determined to provide insight into the motives, the sense of values, and the degree of significance students give their personal and parental circumstances, as factors influencing decision-making.